Kebenaran dan Tanggung Jawab dalam Praktik Kepemimpinan: Studi Filosofis tentang Etika di Perusahaan: A Study Systematic Literature Review - Haribowo, Siget Fitrianto; Winarno, Agung (FEB Universitas Maritim Semarang, 2024)
Truth and responsibility are fundamental ethical principles that shape leadership practices in corporate settings. This study explores the philosophical foundations of truth and responsibility and their applications in leadership ethics within organizations. Using a systematic literature review approach, the research synthesizes findings from various philosophical schools, such as deontology, utilitarianism, and virtue ethics, to examine how leaders can navigate ethical dilemmas, foster integrity, and build trust. The results reveal that embracing truth and accountability enhances decision-making processes, strengthens organizational culture, and mitigates ethical risks. This study highlights the significance of philosophical reflection in addressing modern leadership challenges, particularly in fostering transparency and ethical responsibility in complex business environments. Future research should focus on integrating these principles into leadership development programs to promote sustainable and ethical organizational growth.